(untitled) (Development Service Industry Management, 2024)
The phenomenon of leadership plays a vital role in the system-wide development of subjects of the hierarchy of socio-economic activity. The level of system perfection of enterprises depends on their understanding, which means their efficiency, effectiveness of activities, and competitiveness of both products and the economic system. The research article discusses these questions and the influence of the leadership phenomenon on the level of system excellence of the enterprise from the standpoint of the "historicity" pattern. Depending on this, the impact can be harmful, neutral, or positive. We believe that leadership in the modern world and, above all, in artificial organizational systems, which includes the enterprise, is the ability to form people’s thinking that they have the power to create changes, to think globally - to act locally (as the great Ukrainian Havrylyshyn B. D.). Their result depends exclusively on the activity of each within the framework of the given system-wide direction of functioning and development, even with the necessary creation of conditions for this. Naturally, a system aimed at system-wide development imposes certain restrictions on the manifestations of people in various social roles, including their regressive signs of culture "as an image of life." However, the attractiveness of changing the paradigm to a critical point, which will make it possible to achieve systems of different levels and purposes, including business entities and each of their active elements (people), on the way to change the influence on achieving system perfection from negative to neutral, and with from neutral to positive - fully justify the spent efforts and resources, because it will provide an additional opportunity for systemic development, increasing effectiveness and efficiency, competitiveness in general.